Seismic Hazard Evaluation of the North and Northwest Iranian Plate Considering the Bayesian Perspective - Mehdi Maleki; Zohreh Sadat Riazi Rad (Shock and Vibration)
In the last hundred years alone, there have occurred more than 2000 earthquakes larger than 4 in the northern and northwestern parts of Iran. Because Iran is placed in the heart of the Alpine-Himalayan collision zone, which is one of the world’s greatest seismic locations, massive earthquakes have regularly struck the country. Seismic hazard assessment is a realistic and helpful method for engineering seismology to prevent motions in a location in order to forecast the occurrence of earthquakes. For parameter estimation in seismic hazard assessments, the Bayesian probability theory provides a practical and accurate technique. As a result, Bayesian techniques for analysis are based on an older method. Furthermore, they have the unique capacity to account for the variability of characteristics in probabilistic relationships. In this assessment, we used the Bayesian earthquake risk estimation program developed by Lyubushin. Our research is in the sequence of applications of this program to assess the risk of earthquakes in various parts of the universe. In this method, the basic assumption is that earthquakes follow the characteristic of being Poisson. Its zoning map is drawn in the north and northwest regions of Iran. The highest value was obtained for the city of Tabriz with 0.29 galls, and the lowest value was obtained for the city of Zanjan with the value of 0.06 galls.